A rare case of acute abdomen in the adult: The intestinal duplication cyst. case report and review of the literature. (April 2019) - Ricciardolo, Andrea Aurelio; Iaquinta, Tommaso; Tarantini, Alessandro; Sforza, Nicola; Mosca, Donatella; Serra, Francesco; Cabry, Francesca; Gelmini, Roberta
Abstract: Introduction: Duplications of the gastrointestinal tract are rare congenital anomalies that can occur anywhere throughout the gastrointestinal tract. The reported incidence is 1/4500, and more than 80% occurs before the age of two as an acute abdomen or bowel obstruction. The most common site is Ileum (60%), while the colonic localisation is reported between 4 and 18%. Presentation of the case: Herein we report the case of a 35-year-old man, presented at the Emergency Department with fever and localised abdominal pain in the right iliac fossa. Preoperative abdominal ultrasound and CT scan showed a cystic mass of 44 × 43 × 70 mm adjoining the posterior wall of the right colon. He underwent explorative laparoscopy, laparotomy conversion, right hemicolectomy with an intra-operative diagnosis of colonic duplication cyst, confirmed by histology. Discussion: The review of the literature showed as the intestinal duplication cysts are rare congenital anomalies. The clinical presentation is variable and depends on the site and the related complications. A surgical approach based on the resection of the involved bowel tract is the treatment associated with the best long-term outcomes. Conclusion: It is important to include intestinal duplication in the differential diagnosis of acute abdomen, to ensure the best therapeutic strategy. Highlights: Duplications of the gastrointestinal tract are rare congenital anomalies. The resection of the involved bowel tract is the treatment associated with the best long-term outcomes. It is important to include intestinal duplication in the differential diagnosis of acute abdomen.